Impact of heat and mass transfer in casson trihybrid nanofluid flow past an inclined cylinder, along with the effect of Soret and Dufour - Stepha, N. Golden; Lakshmi, M.; Khan, Ilyas; İnç, Mustafa (Elsevier B.V., 2026)
The investigation of Casson trihybrid nanofluid flow and the heat and mass transfer properties on an inclined cylinder is related to the present study. Such an investigation encompasses the interaction among magnetohydrodynamics (MHD), porous-medium resistance, heat generation, thermal radiation, and cross-diffusion. The objective is to examine the body's parameters in relation to their influence on the transport process, and to compare water, hybrid nanofluid, and trihybrid nanofluid to establish the magnitude of improvement in thermal and mass transfer. Similarity transformations are then used to simplify the governing partial differential equations into a system of ordinary differential equations, and the results are obtained numerically using bvp4c, an inbuilt MATLAB solver. Previously published investigations and analyses support the model, and it is highly consistent with it. The results reveal that velocity decreases with the MHD Casson parameter, and the curvature parameter enhances the velocity distribution. Trihybrid nanofluids, blending multiple nanoparticles, deliver superior thermal conductivity and stronger convective heat transport than conventional formulations. Casson fluid behaviour and cylinder inclination together enhance mixed convection, while Soret and Dufour effects couple heat and mass transfer through cross-diffusion. From the comparative study of the base fluid, nanofluid, hybrid nanofluid, and trihybrid nanofluid, it can be concluded that the trihybrid nanofluid shows the most improvement in transport properties by yielding the highest skin-friction coefficient, Nusselt number, and Sherwood number. Thus, trihybrid nanofluids offer great potential for enhancing heat and mass transfer and can be used in more sophisticated thermal management systems and energy applications, including biomedical fluid transport. © 2026 The Authors.
Keywords: Casson fluid; Dufour effect; Inclined cylinder; Radiation; Soret effect; Trihybrid nano